انسانی نفسیات:قرآن و حدیث کی روشنی میں ایک مطالعہ (Al-Qamar, 2020)
Psychology is the scientific study of mind and behavior. Psychology involves the study of conscious and unconscious phenomena, including feelings and thoughts. It is an academic field of immense breadth, crossing the boundaries between the natural and social sciences. Psychologists seek to understand the emergent properties of the brain, linking the discipline to neuroscience. As social scientists, psychologists aim to understand the behavior of individuals and groups. The first letter of the Greek word psyche, from which the term psychology is derived, is commonly associated with science. The foundation of Islam is based on Quran and Sunnah. Be it Quranic teachings or the fragrant flowers of Seerat Tayyaba. These are the best remedies for character building, caste formation and society formation. Good manners, mercy, justice, economics, political science, psychology and medicine, because the teachings of the Prophet ﷺ have blessings in every aspect of life. Of course, it is not possible to save people from all their problems and diseases, to heal the body and soul without the death of the Messenger of Allah. Physical health and energy, mental purity and gentleness, spiritual maturity and purity, reformation of intentions and intentions and greatness and elevation of character are the essential fruits of Aswa Hasna which have been needed in every age and will always be. Therefore, the statement is divine: لقد کان لکم فی رسول اﷲ اسوۃ حسنہ “Verily, it is better for you to follow the Messenger of Allah).” Human psychology knows its origin and reality better than Allah Almighty, who created man, but psychology is actually the name of that entity which is with everything, whether it is a human being or an animal. Allah Almighty says in the Holy Qur'an about the nature of man. That Allah, the Highest, after creating the universe, has made man the best of all creations, and he will be able to find every pleasure in this world and the hereafter according to his own self. In fact, there are many types of self and there are also many periods, for example, the thinking of a child in childhood will be different from the period of his boyhood and the thinking of his youth will be very different from that of his old age. The main reason for choosing this topic is the psychological disease that mankind is suffering till today.
Keywords: Human Psychology; Quran; Hadith; Light